2007
DOI: 10.1186/ar2338
|View full text |Cite
|
Sign up to set email alerts
|

Activator protein 1 (Fos/Jun) functions in inflammatory bone and skin disease

Abstract: Activator protein 1 (AP-1) (Fos/Jun) is a transcriptional regulator composed of members of the Fos and Jun families of DNA binding proteins. The functions of AP-1 were initially studied in mouse development as well as in the whole organism through conventional transgenic approaches, but also by gene targeting using knockout strategies. The importance of AP-1 proteins in disease pathways including the inflammatory response became fully apparent through conditional mutagenesis in mice, in particular when employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
223
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(235 citation statements)
references
References 52 publications
8
223
0
4
Order By: Relevance
“…Jun proteins were recognized as important regulators of cytokine expression and immune response (13). The function of Jun proteins within the AP-1 complex crucially depends on the cellular context.…”
Section: Systemic Lupus Erythematosus (Sle) Is a Complex Autoimmune Dmentioning
confidence: 99%
“…Jun proteins were recognized as important regulators of cytokine expression and immune response (13). The function of Jun proteins within the AP-1 complex crucially depends on the cellular context.…”
Section: Systemic Lupus Erythematosus (Sle) Is a Complex Autoimmune Dmentioning
confidence: 99%
“…JNKs can activate Jun proteins. 34 In the present study, we found elevated JNKs and c-Jun activities in the skin of Ikka À/À mice, and we found that the transgenic IKKa or reduced EGFR repressed these activities in an IKKa dosedependent manner. Thus, the enhanced JNK and c-Jun activities may contribute to the epidermal hyperplasia, skin inflammation, and tumorigenesis in IKKa-deficient mice.…”
Section: Discussionmentioning
confidence: 48%
“…33,34 The EGFR/HB-EGF pathway is important for the AP-1 pathway in maintaining skin homeostasis. Jun/AP-1 proteins also regulate the expression of cytokines, such as IL-6 and TNFa.…”
Section: Discussionmentioning
confidence: 99%
“…AP-1 is a dimer of the Fos and/or Jun proteins, and it regulates the expression of a broad variety of genes (12). The target genes of AP-1 play important roles in proliferation, differentiation, and apoptosis (13). The expression of AP-1 is tightly linked to mitogenic stimulation, and this finding suggests that AP-1 performs essential functions in cell proliferation.…”
mentioning
confidence: 81%
“…INK4A (13). AP-1 is essential for the expression of the IL-2 gene in response to TCR/CD28 stimulation; therefore, AP-1 is intimately involved in T cell proliferation (15,16).…”
mentioning
confidence: 99%